Managing uncertainty in oncology visits: communication practices with ethnically diverse patients in the Italian medical context - Alby, Francesca; Fatigante, Marilena; Zucchermaglio, Cristina (Psychology Hub, 2024)
Introduction: In the context of a set of oncological visits carried out by one doctor with Italian and migrant patients, this study focuses on how the oncologist refers to, and how he manages, information, which qualify some events as uncertain or not fully predictable. Examples include the patient’s advantage or disadvantage to opt for a certain treatment, the chance to recover from cancer or, on the contrary, the risk of cancer recurrence, as well as the risk to undergo certain side effects of the treatment. Method: Drawing on results obtained by previous coding of 19 videorecorded doctor-patient consultations with native Italian patients and migrant patients, the study applies Conversation Analysis to analyze two single contrastive cases, respectively, with an Italian patient and a Ukraine patient. Results: Analyses reveal that, however the oncologist’s communication is accompanied in both cases by hedging strategies, uncertainty embedded in cancer issues and particularly, in cancer treatment is discussed in much different way in the case of the Italian and the migrant patient. While the Italian patient is addressed with elaborated and detailed information, cast as objects of considered assessment by both the doctor and the patient, the Ukraine patient is addressed with simpler and generic formulations of uncertainty and eventually offered more constrained treatment options. Conclusions: The findings emphasize the importance of exploring the oncologists’ views and perceptions about matters such as: the significance of shared decision making (SDM) in their own practice, the role of the patient’s cultural backgrounds in communicating oncological information, uncertainty and tolerance of ambiguity in the relationship with the patient. .